2013
DOI: 10.1111/jcpe.12092
|View full text |Cite
|
Sign up to set email alerts
|

Validation of reported genetic risk factors for periodontitis in a large‐scale replication study

Abstract: Previous candidate genes carry no susceptibility factors for AgP. Association of IL-10 rs61815643 with AgP is suggested. ANRIL is associated with periodontitis across different populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(115 citation statements)
references
References 37 publications
3
108
2
2
Order By: Relevance
“…Currently, only a fraction of susceptibility genes is robustly identified, namely GLT6D1, ANRIL and COX2, IL1 and IL10 have repeatedly been associated with periodontitis (49,57,58,61,67,(71)(72)(73) AgP and CP (61,70). Probably, the identified SNPs are "genetic markers" and are not the true causative variants for both AgP and CP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, only a fraction of susceptibility genes is robustly identified, namely GLT6D1, ANRIL and COX2, IL1 and IL10 have repeatedly been associated with periodontitis (49,57,58,61,67,(71)(72)(73) AgP and CP (61,70). Probably, the identified SNPs are "genetic markers" and are not the true causative variants for both AgP and CP.…”
Section: Discussionmentioning
confidence: 99%
“…The associations between AgP and SNPs in the CDKN2B antisense RNA 1 (ANRIL) locus can be considered as the best replicated genetic associations in periodontitis to date (Table 1) (61,(71)(72)(73). The interest for the ANRIL locus is based on pleitropy, since this locus was first the best replicated gene locus for cardiovascular diseases, in particular coronary artery disease in Caucasians (71).…”
Section: Anril On Chromosomementioning
confidence: 99%
“…37 A recent large-scale replication study also suggested that only IL-10SNP(rs 61815643) was associated with Dutch and German/Austrian AgP samples. 38 Claudino et al 39 studied the effect of IL-10(-592) gene polymorphism on cytokine expression in 116 CP patients and 173 control subjects. In CP, a significantly lower IL-10 mRNA expression was verified in both CA and AA genotypes when compared to CC genotype carriers.…”
Section: Discussionmentioning
confidence: 99%
“…15 See Tables IV and V in the Data Supplement for gene names, SNPs, genotypes, and association statistics of the associated genetic regions. Potential associations that were observed for genotype data of the immunochip were validated in silico in an independent case-control panel of 159 Dutch AgP cases and 679 population representative Dutch controls as described in 16 . Potential associations that were observed for genotype data of the 500K array genome-wide association study (GWAS) data were replicated using a panel of 424 German AgP cases and 3628 German controls and validated using 159 Dutch AgP cases and 352 periodontal healthy Dutch controls, as described in Table 1.…”
Section: Analysis Of Candidate Genesmentioning
confidence: 99%